Analisis Kesantunan Berbahasa Pada Film Gara-Gara Warisan Karya Muhadkly Acho & Relevansinya Terhadap Pembelajaran Bahasa Indonesia: Kajian Pragmatik - Jelita Br.L Tobing; Adelia Fitri Anggita; Dinda Nur Maulida; Siska Monika Simanjuntak; Yuliana Sari (EDUKASI, 2025)
This study examines language politeness according to Geoffrey Leech's theory in the movie Gara-Gara Pahlawan by Muhadkuri Acho and its implications for Indonesian language learning. The approach used is descriptive qualitative with pragmatic analysis. The data were obtained by using the free listening method and listening to the narration of the characters in the movie. The results of the analysis found 12 data of compliance with the principles of language politeness, consisting of 5 data of the maxim of generosity, 3 data of the maxim of respect, 1 data of the maxim of simplicity, 1 data of the maxim of consensus, and 2 data of the maxim of sympathy. No compliance with the maxim of wisdom was found. This movie is suitable as teaching material for language politeness because it displays many polite speeches and can be a model for choosing the right words according to the context and interlocutors. The application of polite language in learning can improve students' communication skills using polite language in various social situations.